PENGARUH PEMBERIAN SUSU KEDELAI DAN JAHE TERHADAP PENURUNAN KADAR KOLESTEROL WARGA NGARGOYOSO KARANGANYAR - Safitri, Wahyuningsih; Agustin, Wahyu Rima (Universitas Pesantren Tinggi Darul Ulum, 2018)
Individuals with blood cholesterol levels above 200 mg / dl have a risk of heart disease and blood vessels. Utilization of isoflavones contained in soy milk is expected to lower cholesterol levels. Ginger contains a phenolic antioxidant that oleoresin compounds can reduce total cholesterol. The purpose of this study to determine the effect of soy milk and ginger on the decrease in cholesterol levels of citizens Ngargoyoso Karanganyar. his study is a quasi experiment, nonequivalent control group desaign. Technique of sample with purposive sampling. Decreased cholesterol levels measured with GCU Easy Touch. Data analysis with paired sample t-test and independent sample t-test. The mean pretest cholesterol levels in the intervention group were 230.50 mg / dl and in the control group 232.50 mg / dl. The mean postester cholesterol level in the intervention group was 162.90 mg / dl and in the control group 230.00 mg / dl. The independent sample t-test shows p value of 0.000 <0.05. The conclusion of this research is the effect of soy and ginger milk on cholesterol decrease of citizen Ngargoyoso Karanganyar. Keywords: Soy Milk, Ginger, Cholesterol Level.